2009
DOI: 10.1161/circulationaha.109.870774
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activation of Soluble Guanylate Cyclase Protects the Heart Against Ischemic Injury

Abstract: Background-The role of the nitric oxide/cGMP/cGMP-dependent protein kinase G pathway in myocardial protection and preconditioning has been the object of intensive investigations. The novel soluble guanylate cyclase activator cinaciguat has been reported to elevate intracellular [cGMP] and activate the nitric oxide/cGMP/cGMP-dependent protein kinase G pathway in vivo. We investigated the effects of cinaciguat on myocardial infarction induced by isoproterenol in rats. Methods and Results-Rats were treated orall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 40 publications
(37 reference statements)
2
67
0
2
Order By: Relevance
“…The acute phase of myocardial necrosis and dysfunction induced by isoproterenol mimics changes in blood pressure, heart rate, electrocardiogram (ECG), and left ventricular dysfunction similar to that occurs in patients with myocardial infarction. The rat model of isoproterenol induced myocardial infarction offers a reliable non-invasive technique for studying the effects of various potential cardioprotective agents 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The acute phase of myocardial necrosis and dysfunction induced by isoproterenol mimics changes in blood pressure, heart rate, electrocardiogram (ECG), and left ventricular dysfunction similar to that occurs in patients with myocardial infarction. The rat model of isoproterenol induced myocardial infarction offers a reliable non-invasive technique for studying the effects of various potential cardioprotective agents 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Isoproterenol, a beta adrenergic 274 agonist, induces MI in rats [3] and it depletes the energy reserve of cardiac muscle cells, which leads to complex biochemical and structural changes that cause irreversible cellular damage and ultimately infarct-like necrosis [4,5]. The acute phase of myocardial necrosis and repair mimics what occurs in patients: changes in serum enzymes [3], blood pressure (BP), heart rate (HR) [6], electro cardiogram (ECG), histology [3], and matrix metalloproteinase (MMP) in heart tissue [7]. The rat model of isoproterenol-induced MI offers a standardized non-invasive technique for studying the effects of various potential cardioprotective therapies [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although the explanted heart function was recovered from ethanol-induced systolic dysfunction, we showed impaired contractile function 1 h and also unexpectedly 24 h after heart transplantation. In our laboratory, we previously showed in canine orthotopic heart transplantation [37] and cardiopulmonary bypass models of global ischemia/reperfusion [38] and in a rat model of transplantation-induced ischemia/reperfusion injury [14] decreased LV contractility. However, we and others have already demonstrated that 24 h after transplantation systolic and diastolic function return to normal [39,40].…”
Section: Discussionmentioning
confidence: 91%